2019
DOI: 10.1007/s42452-019-0400-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Eichhornia crassipes in the treatment of raw kitchen wastewater

Abstract: The present water crisis mandates the reuse of wastewater for non-potable purpose. In this study, raw kitchen wastewater (KWW) was treated using Eichhornia crassipes, as a low-cost and eco-friendly remediation method. The advantage of Eichhornia crassipes is quick and high efficiency for removal of pollutants from wastewater. It was found that during characterization of raw KWW, the value of pH and the concentration of nitrate nitrogen and ammonium nitrogen were exceeding the permissible limit for irrigation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Regarding the sediment in the polluted water body, the research shows that Lythrum salicaria is suitable as the pioneer plant for removing nitrogen and phosphorus in water when the salinity of sediment is 0%, while Typha orientalis is more suitable as the pioneer plant for removing nitrogen and phosphorus in when the salinity of sediment is 1% (Xiaochuan Liu, 2013). In terms of the biomass and coverage of aquatic plants, taking Eichhornia crassipes as an example, Eichhornia crassipes grows rapidly, which can absorb a large amount of nutrients and heavy metals in the water body and stabilize the pH of the water body (Parwin & Paul, 2019;Tabinda et al, 2019). Relevant studies have shown that when Eichhornia crassipes doesn't endanger the survival of other animals and plants when its coverage rate is below 25%, but it will shield sunlight and reduce the concentration of dissolved oxygen in the water body once it covers the water surface in a large area (Villamagna & Murphy, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the sediment in the polluted water body, the research shows that Lythrum salicaria is suitable as the pioneer plant for removing nitrogen and phosphorus in water when the salinity of sediment is 0%, while Typha orientalis is more suitable as the pioneer plant for removing nitrogen and phosphorus in when the salinity of sediment is 1% (Xiaochuan Liu, 2013). In terms of the biomass and coverage of aquatic plants, taking Eichhornia crassipes as an example, Eichhornia crassipes grows rapidly, which can absorb a large amount of nutrients and heavy metals in the water body and stabilize the pH of the water body (Parwin & Paul, 2019;Tabinda et al, 2019). Relevant studies have shown that when Eichhornia crassipes doesn't endanger the survival of other animals and plants when its coverage rate is below 25%, but it will shield sunlight and reduce the concentration of dissolved oxygen in the water body once it covers the water surface in a large area (Villamagna & Murphy, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In table 5, We found that the most efficient aquatic plant was Eichhornia crassipes where the removal is quantified in N (97.79%), Ammonium (92.03%), BOD5 (77.23%), COD (157.63%), TOC (39.24%), TSS (95.94%), TDS (75.17%), oil and grease (99.33%) in 21 days, It is worth mentioning that this aquatic plant is in high demand for use both for residential discharges and minor housing; however, it was Pistia stratiotes that in a 60-day treatment achieved the removal of Turbidity (98.5%), total N (100%), total BOD (100%) and COD (79.18%) [38] [29].…”
Section: Domestic Wastewatermentioning
confidence: 99%